What's next? : a qualitative study on ESL teachers' experiences of the Covid era and its effects on language education - Atayeva, Aya (2023)
The aim of this research was to study English as a second language (ESL) teachers’ experiences during the global Covid-19 pandemic period and the effects it had in the comprehensive school environment. In addition, the goal was to find out what are ESL teachers’ perspectives on the changes that have been made in ESL teaching during the Covid era. The participants of the study consisted of five ESL teachers from comprehensive schools in Finland and Turkmenistan, all of which were actively teaching throughout the global Covid-19 pandemic. The data was collected through semi-structured open-ended interviews. A thematic analysis research method was used to achieve the study's objectives. In addition, the data was analysed by applying an abductive thematic analysis method. The study revealed that the Covid era had both positive and negative effects on ESL teachers’ experiences. It was also found that both the online ESL teaching model as well as future expectations for ESL teaching have been strongly affected by the global Covid-19 pandemic. In addition, the topic of changes in ESL teachers' cognition, closely related to their teaching practices, has come to light. Research results in this study were aimed at creating awareness of ESL teachers' experiences during the global pandemic and areas for further development among ESL educators.